1968
DOI: 10.1530/jrf.0.0170125
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Motility and Fertility of Spermatozoa Recovered From Different Areas of Ligated Rabbit Epididymides

Abstract: Forty-three males were divided into three experimental groups and ligatures placed unilaterally as follows: (1) on the ductus deferens, (2) on the ductus deferens and corpus epididymidis, and (3) on the ductus deferens, corpus epididymidis and ductuli efferentes. Semen was collected six times a week from all males before ligation and for as long as 12 weeks thereafter. Spermatozoa transported normally from the caput to the cauda epididymidis in non-ligated controls were characterized by rapid migration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…These successive changes alter the morphology of the spermatozoon, so that their properties and functions are also modified while they move along the excurrent ducts (Briz et al, 1995). Some of the distinctive structural changes during spermatozoal maturation are condensation of acrosome (Fawcett & Hollenberg;Bedford, 1964;Bedford & Nicander;Paüfler & Foote, 1968;Hamilton, 1972;Jones et al, 1974;Jones, 1975;Hanks, 1977), reduction in the acrosomal size (Bedford, 1965) as well as loss of the acrosomal components (Holt, 1980). Significant decreases in the dimensional characters of the AC from the epididymal segments in the Black Bengal buck are also consistent with the above findings.…”
Section: Discussionsupporting
confidence: 75%
“…These successive changes alter the morphology of the spermatozoon, so that their properties and functions are also modified while they move along the excurrent ducts (Briz et al, 1995). Some of the distinctive structural changes during spermatozoal maturation are condensation of acrosome (Fawcett & Hollenberg;Bedford, 1964;Bedford & Nicander;Paüfler & Foote, 1968;Hamilton, 1972;Jones et al, 1974;Jones, 1975;Hanks, 1977), reduction in the acrosomal size (Bedford, 1965) as well as loss of the acrosomal components (Holt, 1980). Significant decreases in the dimensional characters of the AC from the epididymal segments in the Black Bengal buck are also consistent with the above findings.…”
Section: Discussionsupporting
confidence: 75%
“…Cytological changes have not been clearly demonstrated after occlusion of the epididymis, although in rabbits the epithelial cells lining the duct become flattened above the site of occlusion (Glover, 1962) and regressive changes in the incarcerated spermatozoa are well documented (Glover, 1962;Orgebin-Crist, 1969;Paufler & Foote, 1969). The effect of epididymal ligation on the function of the lining epithelium will presumably differ from that of efferent ductule ligation, because in the former case spermatozoa, together with rete testis fluid and its contained androgen, will continue to enter the duct, whilst in the other they are prevented from doing so.…”
Section: Introductionmentioning
confidence: 99%
“…
In all mammals studied so far, with the possible exception of man, it has been shown that sperm cells emerging from the testis have to pass through at least part of the epididymis before they acquire the ability to fertilize (Bedford, Calvin & Cooper, 1973;Bedford, 1974).The literature regarding the fertilizing capacity of spermatozoa collected from different segments of the epididymis in laboratory animals has been summarized by Paufler & Foote (1968) and Orgebi n\x=req-\ Crist (1969). Little information is available for the large domestic species although bulls have been successfully inseminated with spermatozoa from the cauda epididymidis (Lardy & Ghosh, 1952;Barker, 1954;Igboeli & Foote, 1968).

The present experiments were therefore conducted to examine the fertilizing capacity of spermatozoa from different regions of the epididymis in the domestic pig.

Text- fig.

…”
mentioning
confidence: 99%
“…The literature regarding the fertilizing capacity of spermatozoa collected from different segments of the epididymis in laboratory animals has been summarized by Paufler & Foote (1968) and Orgebi n\x=req-\ Crist (1969). Little information is available for the large domestic species although bulls have been successfully inseminated with spermatozoa from the cauda epididymidis (Lardy & Ghosh, 1952;Barker, 1954;Igboeli & Foote, 1968).…”
mentioning
confidence: 99%